Regional variation in obstetrical intervention for hospital birth in the Republic of Ireland, 2005-2009 - Lutomski Jennifer E; Morrison John J; Lydon-Rochelle Mona T (BMC, 2012)
Abstract Background Obstetrical interventions during childbirth vary widely across European and North American countries. Regional differences in intrapartum care may reflect an inpatient-based, clinician-oriented, interventional practice style. Methods Using nationally representative hospital discharge data, a retrospective cohort study was conducted to explore regional variation in obstetric intervention across four major regions (Dublin Mid Leinster; Dublin Northeast; South; West) within the Republic of Ireland. Specific focus was given to rates of induction of labour, caesarean delivery, epidural anaesthesia, blood transfusion, hysterectomy and episiotomy. Logistic regression analyses were performed to assess the association between geographical region and interventions while adjusting for patient case-mix. Results 323,588 deliveries were examined. The incidence of interventions varied significantly across regions; the greatest disparities were observed for rates of induction of labour and caesarean delivery. Women in the South had nearly two-fold odds of having prostaglandins (adjusted OR: 1.75, 95% CI 1.68-1.82), whereas women in the West had 1.85 odds (95% CI 1.77-1.93) of artificial rupture of membrane. Women delivering in the Dublin Northeast, South and West regions had more than two-fold increased odds of elective caesarean delivery relative to women delivering in the Dublin Mid Leinster region. The Dublin Northeast region had the highest odds of emergency caesarean delivery (adjusted OR: 1.36; 95% CI: 1.31-1.40). Conclusions Substantial regional variation in intrapartum care was observed within this small, relatively homogeneous population. The association of intervention use with region illustrates the need to encourage uptake of scientific based practice guidelines to better inform clinical judgment.